2010
DOI: 10.1111/j.1469-8749.2010.03764.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐care and mobility skills in children with cerebral palsy, related to their manual ability and gross motor function classifications

Abstract: AIM The aim of this study was to investigate the acquisition of self-care and mobility skills in children with cerebral palsy (CP) in relation to their manual ability and gross motor function.METHOD Data from the Pediatric Evaluation of Disability Inventory (PEDI) self-care and mobility functional skill scales, the Manual Ability Classification System (MACS), and the Gross Motor Function Classification System (GMFCS) were collected from 195 children with CP (73 females, 122 males; mean age 8y 1mo; SD 3y 11mo; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
81
3
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 30 publications
10
81
3
2
Order By: Relevance
“…Although a strong relation has been shown between the higher MACS and GMFCS levels, 25,26 more studies are needed on MACS levels in relation to language comprehension performance.…”
Section: Discussionmentioning
confidence: 99%
“…Although a strong relation has been shown between the higher MACS and GMFCS levels, 25,26 more studies are needed on MACS levels in relation to language comprehension performance.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the lack of movement ability, children with CP spend more energy compared to the same aged healthy children. Due to muscle tone abnormalities, muscle weaknesses, trunk control difficulties and skeletal deformities children with CP are spending up to 2 -3 times more energy compared to the same aged healthy children during a sub maximal exercise [5] [6] [7].…”
Section: Introductionmentioning
confidence: 99%
“…around the seventh year of life (Ohrvall et al, 2010). It has been suggested that the age of 6-7 years is the upper limit for the development of new basic motor skills (Harries et al, 2004;Manikowska et al, 2009) and that by the age of 5 years children have attained 90% of their final functional skills (Manikowska et al, 2009;Natroshvili et al, 2005).…”
Section: Current Rehabilitation Techniques For People With Cpmentioning
confidence: 99%
“…Readers wanting to become more thoroughly acquainted with those scales should refer to suitable literature Grimby, 2004a, 2004b;Barlett and Palisano, 2000;Cavallo et al, 2009;Chiarello et al, 2010;Donkervoort et al, 2007;Gonzalez-Heydrich et al, 2007;Gut and Jabłoński, 2011;Harrison and Oakland 2003;Krigger, 2006;Margre et al, 2010;Michalska et al, 2012;Ohrvall et al, 2010;Østensjø, Carlberg and Vøllestad, 2003;Østensjø et al, 2004;Østensjø et al, 2005;Sienkiewicz et al, 2009;Tarsuslu and Livanelioglu, 2010;Van Eck et al, 2009;Van Eck et al, 2010;Wong et al, 2004). Krigger, 2006;Margre et al, 2010;Ohrvall et al, 2010;Østensjø et al, 2004;Østensjø et al, 2005;Sienkiewicz et al, 2009;Tarsuslu and Livanelioglu, 2010). This scale categorizes an individual's motor functionality according to demonstrated motor skills and age.…”
Section: Current Rehabilitation Techniques For People With Cpmentioning
confidence: 99%